2017
DOI: 10.4172/2155-6148.1000710
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of USG Guided Transversus Abdominis Plane Block for Post- Operative Analgesia in Total Abdominal Hysterectomy Surgeries

Abstract: Introduction and aims: Transversus abdominis plane (TAP) block is a fascial plane block providing postoperative analgesia in patients undergoing surgery with infraumbilical incision. This single blind prospective randomized control study aimed to evaluate the effectiveness of the TAP block for postoperative pain, as part of a multimodal analgesic regimen in patients undergoing TAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…It was observed that a significantly higher number of patients in the epidural group required rescue analgesic and at higher dosages (p<0.05). [22,24,26,27,30] Complications / Adverse effects In the present study, 2 (5.71%) and 3 (8.57%) patients in TAP group and Epidural group respectively had nausea. 1 (2.86%) and 2 (5.71%) patients in TAP group and Epidural group respectively had vomiting and 0 (0%) and 2 (5.71%) patients in TAP group and Epidural group respectively had a headache.The incidence of nausea & vomiting was more in the epidural group as compared to group A, however this difference was statistically not significant as per Chi-Square test (p>0.05).…”
Section: Visual Analog Scale For Painsupporting
confidence: 44%
See 3 more Smart Citations
“…It was observed that a significantly higher number of patients in the epidural group required rescue analgesic and at higher dosages (p<0.05). [22,24,26,27,30] Complications / Adverse effects In the present study, 2 (5.71%) and 3 (8.57%) patients in TAP group and Epidural group respectively had nausea. 1 (2.86%) and 2 (5.71%) patients in TAP group and Epidural group respectively had vomiting and 0 (0%) and 2 (5.71%) patients in TAP group and Epidural group respectively had a headache.The incidence of nausea & vomiting was more in the epidural group as compared to group A, however this difference was statistically not significant as per Chi-Square test (p>0.05).…”
Section: Visual Analog Scale For Painsupporting
confidence: 44%
“…Here, Mean arterial pressure was also significantly lower in the Epidural group as compared to TAP group (p<0.05) from 30 minutes to 8 hours of both the blocks. [20,26,27,30] Duration of Analgesia:…”
Section: Vital Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Atimet al 10 have concluded that opioid is less inultrasound-guided TAP block after TAH than superficial wound infiltration.McDonnell et al 7 showed that TAP block reduce mean IV morphinerequirements more than 70%. Prabu et al 14 showed that TAP block had significantly reduced post-operative morphine consumption at 2,4 and 6 h and also reduced the mean morphine requirement by 57%. Ra et al 15 showed that USG-TAP block could the amount of opioid during operation and 24 hour post-operative period after laparoscopic cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%